Evaluating Integrated Task Based Language Teaching and English Language Learning and Instruction System - Andhi Dwi Nugroho (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aimed at evaluating the implementation of integrated TBLT and ELLIS which emphsized on observing, questioning, exploring, and communicating. The integrated learning had been implemented at two different classes of SMPN 1 Banguntapan and SMPM Piyungan in Bantul regency, Yogyakarta. The task resources were selected from ELLIS units involving sixteen units. Of quesionnaires and interviews, the results indicated that the developed tasks had already met the standard of learning competence at the level. Teachers and students responded in several aspects, namely; learning objective, content material, integrated language skill exercise, and self-evaluation availibility. Thus, the integrated tasks conclusively helped the students achieve better and easier understanding, promotes learning interest, and evaluate their own learning and progress, inasmuch as these tasks equipped with the individual and group exercises. This study implies that combination of TBLT and ELLIS generated better opportunities to create more innovative English teaching.